Pendampingan Belajar Peserta Didik Menggunakan Model Pembelajaran E-Split Classroom untuk Memfasilitasi Kemampuan Literasi Matematika - Mubarak, Ashar; Saputra, Agung Muhtar; Fitriani Nur; Rachmah Ratnaningtiyas; Abrar, Andi Ika Prasasti (KHIDMAH: Jurnal Pengabdian Masyarakat, 2025)
Mathematics education currently continues to face various challenges, especially at MTSN Kota Batu where most students still have low mathematical literacy skills, this is due to the lack of effectiveness of the learning models implemented. Therefore, it is necessary to provide learning assistance so that students can improve their mathematical literacy skills. The community service method used is the Service-Learning method. This learning assistance is carried out with an interactive and comprehensive approach. The aim of this learning assistance is so that students can improve their mathematical literacy skills by implementing the E-Split Classroom learning model. The result of the learning assistance activities that have been carried out is that students' mathematical literacy skills are facilitated, this is proven by an average of 72.7 in the high category. Thus, learning assistance activities are recommended to be carried out periodically and continuously in an effort to face various challenges that exist, especially in the world of mathematics. The follow-up plans that will be carried out include regular learning assistance, teacher training to optimize the E-Split Classroom model, as well as monitoring, evaluation and development of teaching materials to improve students' mathematical literacy skills on an ongoing basis.